Melanoma in prepuberal age. - Rota, C.; Cacciaguerra, M.G.; Palermi, G.; Pedicelli, C.; Annessi, G.; Paradisi, M. (European Journal of Pediatric Dermatology, 2009)
Melanoma below 20 years of age accounts for just 1-3% of all malignancies and is even more rare, between 0.3% and 0.4% in prepuberal age. The extreme rarity and the limited availability of literature data do not clarify the biological behavior or the prognosis of this cancer in young people. Therefore the specific treatment strategies are only based on experience obtained with adults. Many pediatric melanomas are commonly misdiagnosed, both for the very atypical clinical presentation and for the many biases resulting from the extreme rarity, and even for the reluctance to perform invasive interventions such as biopsies or surgical removal. So the reports of any cases of melanoma in early childhood, especially if not arising on a giant congenital nevus, is of both human and professional interest. We present the case of a 3-year-old child who came to our observation after the recent appearance of a reddish nodule on a pigmented lesion of the right groin.